2004
DOI: 10.1097/01.nmd.0000120885.17362.94
|View full text |Cite
|
Sign up to set email alerts
|

Poor Mental Health, Depression, and Associations With Alcohol Consumption, Harm, and Abuse in a National Sample of Young Adults in College

Abstract: The purpose of this article was to describe patterns of poor mental health/depression (PMHD) in a national sample of college students and the relationships among PMHD, alcohol consumption, harm, and abuse. Responses to mailed questionnaires completed by a random sample of 27,409 students at 119 colleges were analyzed using logistic regression. Nationally, 4.8% of students reported PMHD. The average college prevalence was 5.01% (range, 0.68% to 13.23%). Students with PMHD were more likely than their peers to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

14
200
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(225 citation statements)
references
References 30 publications
14
200
2
9
Order By: Relevance
“…Responses to the 6-point Likert-scaled items were transformed to a 100-point scale for analysis, consistent with published reports. 28 Higher values indicated better mental health and values ,40 were considered clinically relevant.…”
Section: Mental Health Statusmentioning
confidence: 99%
“…Responses to the 6-point Likert-scaled items were transformed to a 100-point scale for analysis, consistent with published reports. 28 Higher values indicated better mental health and values ,40 were considered clinically relevant.…”
Section: Mental Health Statusmentioning
confidence: 99%
“…In a random sample of more than 27,400 college students from across the United States, Weitzman (2004) found that students with poor mental health were likely to report frequent, heavy and heavy episodic drinking and were also more likely to drink with the intent of getting drunk. In a similar study, Geisner et al (2004) found that the association between psychological distress and negative drinking consequences was greater for male college students than females.…”
Section: Mental Healthmentioning
confidence: 99%
“…Large American cross-sectional studies have shown that college students suffering from social anxiety disorders report frequent heavy and heavy episodic drinking, and drinking with the intention of getting drunk (Geisner et al 2004;Weitzman 2004). Drinking heavily, in combination with depression, is a significant predictor of suicidal ideation, self-harm and suicide in young people (Windle 2004;Miller et al 2007;Sher 2006).…”
Section: Mental Healthmentioning
confidence: 99%
“…Furthermore, women and men metabolize alcohol differently, which may lead to different blood alcohol levels even when consuming the same amount of alcohol (Thomasson, 1995). However, depressive symptoms are more common in female than male students (Harford et al, 2006;Weitzman, 2004). Preliminary evidence suggests that gender may moderate the relationship between depressive symptoms and drinking behavior.…”
mentioning
confidence: 98%